Thermal Plasticity in Insects’ Response to Climate Change and to Multifactorial Environments - Rodrigues, Yara Katia; Beldade, Patrícia (Frontiers in Ecology and Evolution, 2020)
Phenotypic plasticity, the property by which living organisms express different phenotypes depending on environmental conditions, can impact their response to environmental perturbation, including that resulting from climate change. When exposed to altered environmental conditions, phenotypic plasticity might help or might hinder both immediate survival and future adaptation. Because climate change will cause more than a global rise in mean temperatures, it is valuable to consider the combined effects of temperature and other environmental variables on trait expression (thermal plasticity), as well as trait evolution (thermal adaptation). In this review, we focus primarily on thermal developmental plasticity in insects. We discuss the genomics of thermal plasticity and its relationship to thermal adaptation and thermal tolerance, and to climate change and multifactorial environments.